PENGGUNAAN MEDIA PEMBELAJARAN IPS KELAS VIII DI SMP MUHAMMADIYAH 6 PADANG. - Marissa, Melly; Kaksim, Kaksim; Syamdani, Syamdani (Pendidikan Sejarah, 2013)
ABSTRACTThe uses of media is something that very important in teaching learning process because teacher which qualified necessarily realizes utterly that media one of the place to brainstorm studentâs knowledge to chastened material and removes students bore in teaching learning process. Â Besides that the media that is used by teacher should be concerning with the lesson. Â It means that the media that used by the teacher are able to passing on order that included in the lesson. Â Based on the uses of media above, this research is purpose to see the using of media by History Social Science Education teacher at SMP Muhammadiyah 6 Padang Nanggalo district in second class. The method that uses in this research are qualitative and evaluation method. Â The informan people in this research are headmaster, vice headmaster, history social science teacher, and 10 of student second class. Technique data collections are interview and observation. Â Technique analytical data are collection data, reduction data, display data, and conclusion. The result of the research show that the using of media by History Social Science Education teacher in teaching learning process at SMP Muhammadiyah 6 Padang is not square with the material that taught by the teacher. Â It can show from the media that used is not able to reveal some pacts of history such as: place pact, time pact, and scene pact. Â It cause by some factors such as: insufficiently of tools that used by the teacher, insufficiently of teacherâs knowledge and relationship between teacher and students. Â Usually History Social Science Education teacher at SMP Muhammadiyah 6 Padang only uses map, globe, atlas and chart. Â So, if want to success in teaching learning process the teacher should improve their media.Â Â Key Words: Media by History Social Science Education